ANALISIS STRATEGI AKUISISI DAN RESTRUKTURISASI DALAM BISNIS PERUSAHAAN - HELMALIA HELMALIA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
Companies need to develop an appropriate strategy in order to maintain its presence and improve its performance. One attempt to become a large company and strong is to implement the strategy of acquisitions and restructuring. The advent of the era of free-market impact on the company's business competition is getting tighter. This condition spur businesses to be concerned about the strategy pursued. Even companies continue to attempt to formulate and refine their business strategies in order to win the competition. Acquisition strategy as the dominant means used by companies to develop strategies for diversification and at the time of acquisition contributed to the poor performance, the company may consider the necessity of restructuring operations. With the acquisition and restructuring strategies that run the company is expected to stabilize the company's business so as to reduce the risk of the company.